The Effect of Using The Problem-Based Learning Model on Learning Outcomes of Class VIII Junior High School Students - Salsabila, Salsabila; Sripatmi, Sripatmi; Salsabila, Nilza Humaira; Azmi, Syahrul (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
This research aims to determine the effect of the problem-based learning model on the learning outcomes of class VIII students at SMP IT YARSI Mataram on relationship and function material. The method used is a quasi-experimental method, with a posttest-only group design research design. The sample use in this research is saturated because all members of the population were sampled. The sample used in this research was all 39 students in class VIII of SMP IT YARSI Mataram. The instruments in this research are test question, learning implementation plans, and learning activity observation sheets. Data collection was carried out using test instruments. The research results werw tested for normality with the Liliefors test and homogeneity test with Fisher’s test, then analyzed using the t-test. The result of the t-test analysis show with a significance level of This show that the problem-based learning model affects the mathematics learning outcomes of class VIII students at SMP IT YARSI Mataram. Therefore, the problem-based learning model should be used in learning to improve students’ mathematics learning outcomes.